Artillery - Gander, Terry; Sarson, Peter; Gibbons, Tony; Bryan, Tony (Minneapolis : Lerner Publications, 1987)
Surveys modern artillery in military use, including towed and self-propelled guns, rockets, ammunition, and associated equipment.
Includes index.
Keywords: Ordnance -- Juvenile literature; Artillery -- Juvenile literature